(untitled) (Argos, 2025)
Religions stand as a perspective to observe social processes, pointing out the nature and distribution of political forces while being at the same time an example of the center-periphery. Hecules Gaditanus is the case under study, a example in which converge ethnic and religious elements, and for which we have got a typological variety of sources. Numismatic and epigraphic sources are at the grounding testing, which come from an original locus: Gades. Afterwards are considered testimonies coming from Rome in order to analyze how Hercules Gaditanus makes its appearence at the imperial capital, that is, how does it mirror at the center this fact originated at the periphery.